The Improvement in Surface Properties of Metallic Implant via Magnetron Sputtering: Recent Progress and Remaining Challenges - Akhtar, Memoona; Uzair, Syed Ahmed; Rizwan, Muhammad; Ur Rehman, Muhammad Atiq (Frontiers in Materials, 2022)
Bioceramic coatings on metallic implants provide a wear-resistant and biocompatible layer, that own ability to develop bone-like apatite in physiological environments to ensure bonding with hard tissues. These bioceramics primarily belong to Calcium Phosphates (CaPs), bioactive glasses, and glass-ceramics. Several techniques are used to deposit these coatings such as; electrophoretic deposition (EPD), plasma spray (PS), and Radio frequency magnetron sputtering (RFMS). Most of these techniques require a high-temperature operation or sintering treatment. This causes either thermal decomposition of bioceramic or results in delamination and cracking of the bioceramic coating due to differences in thermal expansion behavior of metals and bioceramics. RFMS is primarily carried out either at room temperature. However, annealing is performed or substrate is heated at various temperatures ~`400oC- 1200oC for 2 or 4 hours under dry argon (very low temperature compared to other techniques) to ensure crystallization of bioceramics and improve coating adhesion. Chemical composition stability and excellent surface finish are the premium features of RFMS, due to less heat involvement. Moreover, RFMS has the unique ability to develop one-unit/ multilayered composite coatings and the flexibility of in-situ reactions to yield oxides and nitrides. Single or multiple targets can be employed with the insertion of Oxygen and Nitrogen to yield versatile coatings. Due to this attractive set of features RFMS has a strong potential in the field of bioceramic coatings. In recent years, several multifunctional bioceramic coatings have been deposited on metallic substrates using RFMS for biomedical applications. This review focuses on the recent efforts made in order to deposit multifunctional bioceramic RFMS coatings with surface characteristics necessary for biomedical applications and highlights future directions for the improved biological performance of RFMS bioceramic coatings.